Pertussis Immunization During Pregnancy: Assessment of the Role of Maternal Antibodies on Immune Responses in Term and Preterm-Born Infants. (10th May 2021) - Maertens, Kirsten; Orije, Marjolein R P; Herzog, Sereina A; Mahieu, Ludo M; Hens, Niel; Van Damme, Pierre; Leuridan, Elke
Abstract: Background: Limited data exist on the impact of maternal tetanus, diphtheria, acellular pertussis (Tdap) vaccination for preterm born infants. We report its effect at birth and on antibody-mediated immune responses to a DTaP-IPV-HB-PRP T vaccine in preterm compared with term infants. Methods: Women delivering at term or prematurely were either vaccinated with a Tdap vaccine (Boostrix; GSK) during pregnancy or not vaccinated in the last 5 years. Cord and maternal blood were collected at delivery. Infants were vaccinated with DTaP-IPV-HB-PRP T vaccine (Hexyon; Sanofi Pasteur) and blood collected before and 1 month after primary (8-12-16 weeks) and before and 1 month after booster vaccination (13 or 15 months for preterm and term, respectively). Immunoglobulin G antibodies against all antigens included in DTaP-IPV-HB-PRP T vaccine were measured (NCT02511327). Results: Cord blood geometric mean concentrations (GMCs) in preterm infants from Tdap-vaccinated women were significantly higher than in term and preterm infants from unvaccinated women. A longer time interval between maternal vaccination and delivery resulted in higher cord blood GMCs in preterm infants. Equal GMCs in term and preterm infants from Tdap-vaccinated women were observed after primary vaccination. After boosting, significantly lower GMCs were seen for pertussis toxin, filamentous hemagglutinin, and tetanus toxoid in preterm compared with term infants from Tdap-vaccinated women, yet still comparable to GMCs in both term and preterm infants from unvaccinated women. Conclusions: Preterm infants profit from maternal Tdap vaccination. Prematurity did not influence primary immune responses in the presence of maternal antibodies but was associated with a lower booster immune response. Abstract : Preterm infants profit from maternal Tdap vaccination. Vaccination earlier in pregnancy is better to protect both term and preterm infants. Preterm infants mount favorable antibody-mediated immune responses in the presence of vaccine-induced maternal antibodies.